Variabilidade genética no germoplasma de melão da agricultura tradicional do Nordeste brasileiro - Amorim, Clisneide Coelho de (2021)
Traditional agriculture in Brazil is a rich source of germplasm, however, there is little information about the genetic variability that exists in this type of cultivation, including the germplasm of melon (Cucumis melo L.) from family farming that is stored in the Active Germplasm Bank of Cucurbits for Northeastern Brazil. Thus, the objective of this work was to estimate the genetic diversity among the melon germplasm, using different multivariate analysis techniques. Twenty sub-accessions were evaluated, in two field experiments, in randomized complete blocks with three replications, obtaining progenies S1 and S2. For the characterization, 12 quantitative and 11 qualitative descriptors were used. The means of the quantitative descriptors were grouped by the Scott Knott test at 5% significance and from the joint data (quantitative and qualitative descriptors) the dissimilarity matrix was formed and, then, the data were grouped by the methods UPGMA, Tocher and Ward-MLM. There was a significant difference at the level of p <0.01, for all quantitative descriptors analyzed, except for the thickness of the fruit pulp in the right side. For the two types of progenies and the three applied statistical methods, groups (10 of them) were formed that separated the three botanical varieties. There is variability among and within the studied sub-accessions and the UPGMA and Tocher methods were more efficient in estimating the genetic diversity between melon accessions in family farming.